An Essay on Whether We Can Train Bots to Become Virtual Teaching Assistants? And What Can Negotiators Learn as We Do? - Dwight Golann (Washington University Journal of Law and Policy, 2026)
Artificial Intelligence (AI) provides potentially unlimited tools to enhance legal teaching, especially in the fields of negotiation and mediation. “Bots” are one such tool: tireless teacher’s assistants, able to guide students through the process of negotiation and teach them skills needed to be an effective legal bargainer. Building such bots presents a challenge, however, because AI systems are designed to provide users with information and assistance. As a result, although bots can negotiate without training, they are often ineffective bargainers: divulging information, offering concessions, and allowing themselves to be exploited by competitive bargainers. This Essay explores how to train bots to “negotiate like lawyers,” able to adapt tactics to individual situations and what occurs in the process, and moving as needed between a cooperative or competitive stance. It also provides step-by-step instructions to create a bargaining bot in ChatGPT. The author notes that texts on negotiation, as well as his own teaching methods, do not give students specific advice about what to do in different bargaining situations, such as how specifically to frame an opening offer in settlement negotiations or dealmaking. He describes how the process of training bots prompted him to explore his own often unconscious “rules of bargaining.” The author concludes that AI bots offer exciting new tools to deepen our understanding of bargaining and improve negotiation outcomes.
Keywords: #LegalTechPedagogy; #AILegalEducation; #NegotiationBots; #BargainingBots